Kecemasan Sosial dan Ketergantungan Media Sosial pada Mahasiswa - Fatih Azka; Dendih Fredi Firdaus; Elisa Kurniadewi (Psympathic : Jurnal Ilmiah Psikologi, 2018)
This study aims to examine the effect of social anxiety on social media dependence in university students. This research used the quantitative approach with a predictive correlation method. The instruments were social anxiety scale (92 items) refers to aspects of social anxiety from La Greca and Lopez, and the scale of dependence on social media (30 items) refers to Griffiths. The participants were 342 students of UIN Sunan Gunung Djati Bandung selected by random sampling. The results show that social anxiety influence dependence on social media in university students. The influence of social anxiety variables to dependence on social media is about 7.2%. Most of the participants have social anxiety and social media dependence in the medium category.